Intravenous antibiotics reduce the presence of Aspergillus in adult cystic fibrosis sputum. Issue 7 (19th March 2013) - Baxter, Caroline G; Rautemaa, Riina; Jones, Andrew M; Webb, A Kevin; Bull, Matthew; Mahenthiralingam, Eshwar; Denning, David W
Abstract : Background: Pseudomonas aeruginosa and Aspergillus fumigatus frequently co-colonise the airways of patients with cystic fibrosis (CF). This study aimed to assess the impact of short-term administration of intravenous antipseudomonal antibiotics during CF exacerbations on the presence of Aspergillus . Methods: Pre- and post-antibiotic sputum samples from 26 adult patients with CF and chronic Pseudomonas colonisation were analysed for the presence of Aspergillus by fungal culture, real-time PCR and galactomannan antigen (GM). Lung function (forced expiratory volume in 1 s and forced vital capacity % predicted) and blood levels of total IgE, specific A fumigatus IgE and specific A fumigatus IgG were measured at the start and end of antibiotics. Respiratory viral real-time PCR and bacterial community profiling using ribosomal intergenic spacer analysis (RISA) were performed to estimate concurrent changes in the lung microbiome. Results: Aspergillus PCR and GM were more sensitive than culture in detecting Aspergillus species (culture 8%, GM 31%, PCR 77%). There was a significant decline in the presence of Aspergillus, measured both by PCR and GM index, following antibacterial therapy (PCR: median increase in crossing threshold 1.7 (IQR 0.5–3.8), p<0.001; GM: median fall in GM index 0.7 (IQR 0.4–1.6), p=0.016). All patients improved clinically with a significant increase in lung function (p<0.0001). RISA community analysis showed large changes in bacterial community similarity in 67% of patients following antibiotics. Viral RT-PCR demonstrated the presence of a concurrent respiratory virus in 27% of patients. Conclusions: Intravenous antibiotics targeting Pseudomonas during CF pulmonary exacerbations have a negative impact on the presence of Aspergillus in sputum samples.